DINAMIKA KERAGAAN KEMISKINAN DI DESA PATANAS DAN UPAYA MENGATASINYA - Valeriana Darwis (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
Poverty reduction  is a priority  development agenda  and  a lot of  programs or  policies  that  have  been  implemented  by  the  government.  One  of  the  pockets  of poverty  are  diperdesaan  where  people  work  in  the  agricultural  sector.  In  locations irrigated  rice  agro-ecosystem  study  the  performance  of  rice-based  poverty  in  2007 and 2010  experienced a  negative growth,  it is seen from: (i)  reduced  employment  and increased  unemployment,  (ii)  a source  of income  from  agriculture  generally,  but  she became  a source  of income  in  non-agriculture,  (iii)  land  ownership  between  0.25 to 1 ha  and  reverse  the  decline  of arable land  rent  is increasing,  (iv)  expenditure  on food increased  primarily  to  meet  the  needs  of  carbohydrates  and  animal  sources.  The dynamics of  the most  positive  efforts  made  respondents  in addressing  the problem of food  by  way  of  debt,  overcoming  difficulties  by  reducing  the  amount  of  clothing purchases,  overcoming  difficulties  fulfilling  its way into  participants  health  insurance for the poor,  addressing  educational  problems  by borrowing  money  or  do not  attend school.